Reevaluation and Delineation of Protected Areas in the Framework of Optimizing the Implementation of Protected Areas of Nunukan Island In the Nunukan District of North Kalimantan Province - Eko Sulistiono (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
This research has purpose (1) setting back the position of forest conservation in Nunukan Island that is free from the settlement, encroachment population, and also the location of public facilities from local community, (2) Knowing conflict matter of tenure and social that is accumulate so the forest conservation in Nunukan Island that is needed has function as water infiltration and water function for the life of Nunukan Island Community overall.The object research consists of doing the scoring in Nunukan Island by paramaters (1), the slope, (2)  the land cover, (3) the population density and the rain intensity. Based on the score of scoring four (4) parameters so it will get the location that should be the forest conservation in Nunukan Island.Based on the analysis result by the processing of scoring sum, it can not be gotten the score that shows over 175. But the determination of forest conservattion in Nunukan Island  can be gotten from the class of the field slopes >  40% the width is 871,48 hectares and the type of land organosol slope > 15 % the width is 1.4777,28 hectares and the spring 9,62 hectares. Based on the fact that Nunukan Island as residential areas needs the availability of water for the special necessities that is set by the government. It will be submitted by Directorate General of Forestry, agriculture as forest conservation , so it is needed to set the forest conservation area in Nunukan Island to ensure the availability of clean water for the community needs.Tarakan merupakan satu-satunya Kota serta sekaligus Pulau kecil di Provinsi Kalimantan Utara yang memiliki kawasan hutan tersisa relatif sempit. Sejak tahun 2007 Pemerintah Kota melalui Dinas Kehutanan (sekarang bernama Dinas Kehutanan, Pertambangan dan Energi) berkeinginan kuat merintis kawasan hutan guna dijadikan Kesatuan Pengelolaan Hutan Lindung (KPHL). Keinginan Tarakan membentuk KPH direspon baik oleh Kementerian Kehutanan dengan menerbitkan SK Menhut No. 783/Menhut-II/2009, dimana Tarakan sebagai salah satu lokasi implementasi model Kesatuan Pengelolaan Hutan.